2015
DOI: 10.1111/1365-2745.12474
|View full text |Cite
|
Sign up to set email alerts
|

A deteriorating state of affairs: How endogenous and exogenous factors determine plant decay rates

Abstract: Summary Woody plants store large quantities of carbon (C) and nutrients. As plants senesce and decay, these stores transfer to the soil or other organisms or are released to the atmosphere. Exogenous factors such as topographic position and microclimatic and edaphic conditions tied to locations affect decay rates; however, we know less about how exogenous relative to endogenous factors such as morphological, anatomical and chemical construction tied to plant species affect these rates, especially across diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 80 publications
(192 reference statements)
4
103
0
1
Order By: Relevance
“…For every replicate, we measured initial wet mass. We then estimated initial dry mass from the dry mass to wet mass ratio (DMWMR) of additional segments that we collected from each harvested stem and dried to constant mass at 103°C (Zanne et al, ). The first cohort was deployed in 2009 and included wood from 16 species.…”
Section: Matierals and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For every replicate, we measured initial wet mass. We then estimated initial dry mass from the dry mass to wet mass ratio (DMWMR) of additional segments that we collected from each harvested stem and dried to constant mass at 103°C (Zanne et al, ). The first cohort was deployed in 2009 and included wood from 16 species.…”
Section: Matierals and Methodsmentioning
confidence: 99%
“…Ca, log(P), and Mn; Zanne et al, ). Anatomical traits were wood density, conduit lumen diameter (Zanne et al, ), and conduit length (Oberle, Ogle, Zuluaga, Sweeney, & Zanne, ). We also measured the fraction of cross‐sectional area represented by parenchyma and conduit walls based on microscopic analysis of radial sectors of fixed, stained cross sections from three branches per species following the same methodology as (Osazuwa‐Peters, Wright, & Zanne, ).…”
Section: Matierals and Methodsmentioning
confidence: 99%
“…As discussed in the previous section, there is growing evidence that environmental conditions determine SOM stabilization mainly through accessibility of substrate for microorganisms (von Lützow et al, 2006;Dungait et al, 2012;Marschner et al, 2008;Klotzbücher et al, 2011). Zanne et al (2015) however found that effects related to species and tissue construction overruled exogenous effects on wood decomposition. Despite the lack of knowledge on specific driver effects on SOM stabilization, the current literature on main environmental and substrate-specific drivers of C respiration loss in forest soils and CWD will be reviewed in the next paragraphs.…”
Section: Environmental Drivers Of Decomposition and Soil Carbon Stabimentioning
confidence: 99%
“…These substrate factors may explain differences in decomposition rates among species and among tissues within an individual (Zanne et al, 2015). A full overview of all relevant species-specific properties is beyond the scope of this review, but an extensive overview of substratespecific drivers of decomposition can be found in Cornwell et al (2009).…”
Section: Substrate-specific Properties Driving Decomposition Processmentioning
confidence: 99%
“…That said, the total amount of CWD in a given forest varies greatly with species composition, stand age, tree size, temperature, and humidity [29,33]. Moreover, landscape features such as slopes and valleys affect CWD spatial distribution and decomposition, with logs tending to move downhill where they are also susceptible to more rapid decay [34,45].…”
Section: Characteristicsmentioning
confidence: 99%